Pelatihan Dual Task Exercise untuk Meningkatkan Keseimbangan Lansia - Astrid Komala Dewi; Catherine Hermawan Salim; Ria Efkelin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Elderly people experience a decline in physiological function, particularly in the musculoskeletal and neuromotor systems, which can lead to balance disorders and increase the risk of falls. One physiotherapy intervention that can be used to improve balance in older adults is dual-task exercise, which combines motor and cognitive activities simultaneously. This study aimed to determine the effect of dual-task exercise training on improving balance in older adults.The research method used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of older adults who met the inclusion criteria and were given dual-task exercise intervention for several weeks at a specific training frequency. Balance measurements were performed using instruments such as the Berg Balance Scale (BBS) or the Timed Up and Go Test (TUGT). Data were analyzed using statistical tests to determine differences before and after the intervention.The results showed a significant improvement in balance after dual-task exercise training. This training improved coordination, postural control, concentration, and the ability of older adults to perform daily activities involving multiple tasks. Furthermore, dual-task exercise training also helped improve the sensorimotor system's ability to adapt to balance disorders.The conclusion of this study is that dual-task exercise training is effective in improving balance in the elderly and can be used as a physiotherapy intervention to reduce the risk of falls in the elderly population.